IMPLEMENTASI PI-HOLE UNTUK MEMBANGUN SISTEM PERTAHANAN JARINGAN DARI SERANGAN MALVERTISING - Nindya Dwi Anggana; Dedi Hariyadi; Rama Sahtyawan; Alfun Roehatul Jannah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2022)
The Internet has revolutionized human activities in the digital era, providing new avenues for innovation and connectivity. Online advertising, a significant aspect of this digital landscape, enables advertisers to reach diverse audiences. However, this convenience has also attracted cybercriminals who exploit online advertisements to deploy malicious ads, commonly known as malvertising. This study focuses on implementing Pi-Hole, a network defense system, to combat web-based malvertising attacks and reduce associated risks. Utilizing a Raspberry Pi 3 model B+ device, the Pi-Hole system is deployed within the DMZ network at FTTI Universitas Jenderal Achmad Yani Yogyakarta. By capturing query logs, Pi-Hole effectively blocks malicious ads by employing an adlist. The research was conducted over a 14-day period, from July 26 to August 8, 2022. The results demonstrate the efficacy of the Pi-Hole defense system, with a remarkable 22.7% of the total captured queries, amounting to 895,077 queries, being successfully blocked. Additionally, testing from the client's perspective confirmed the system's ability to prevent ads from appearing on websites and mobile applications. The implementation of Pi-Hole on the FTTI network at Jenderal Achmad Yani Yogyakarta University provides a robust defense against malvertising attacks. By blocking malicious ads, Pi-Hole safeguards users' browsing experiences and reduces the risk of potential harm from online advertisements. This research contributes to the growing body of knowledge on network security and offers practical insights for organizations and individuals seeking effective measures to counter web-based malvertising attacks.